Implementing Two Dimensions Decentralized Carrier Phase Shift Method for Multicell Serial-Parallel Inverters - Phu Cong Nguyen; Quoc Dung Phan; Tuyen Dinh Nguyen (IEEE Open Journal of Power Electronics)
With regard to the research and application of power converters, scientists have focused on finding structures and researching control solutions for multilevel multiphase power converters (MMC). Connecting cells in series, parallel (2 Dimension-2D) to the MMC allows easy adjustment of the power and output voltage. The design of MMCs must ensure that the switching voltage is less than the switching voltage limit of the insulated gate bipolar transistor (IGBT), and that the 2D structure can easily adjust the voltage at each level by adding or removing several cells in series. A 2D structure can be designed for a wide power range, which can be quickly achieved by adjusting the number of cells (or multicell branches) in parallel. Currently, the use of 2D structures has only a few published studies on the aspect of DC/DC modulation. This study implements a decentralized carrier phase angle shift algorithm for multicell power converters coupled in series and parallel to supply single-phase alternating current (AC) loads. This paper proposes and verifies an algorithm to ensure that the carrier phase angles of cells in the 2D structure are evenly alternating, thereby improving the algorithm to balance the alternating current between parallel branches connecting the load. Reviews, analyses, and assessments were verified on a 2D structure simulation model including six parallel branches, each of which has six cells in Matlab/Simulink software, and verified by an experimental model including four branches, each of which has four cells using digital signal processing (DSP) TMS320F28379D as the controller.